Eurasian Intermodal Supply Chains : a Dynamic Systems Approach - Hilmola, Olli-Pekka; Panova, Yulia (Cambridge Scholars Publishing, 2020)
In the forthcoming decades, Eurasia will be a place of new growth and prosperity. China is rapidly increasing international infrastructure investments, such as stimulating the One Belt One Road Programme (or the Belt and Road Initiative) which will serve different European cities. This book covers block trains, intermodal and multimodal transport, piggyback transport, single-wagon transport and other types of freight traffic, offering an up-to-date, Eurasian perspective filled with many cases and models (with software re-creating the real world) that help the reader to understand the dynamics.